Shear Banding in Binary Cu-Zr Metallic Glass: Comparison of the G-Phase With L-Phase - Shen, Yidi; Johnson, William L.; Samwer, Konrad; Corona, Sydney L.; Goddard, William A.; An, Qi (Frontiers in Materials, 2022)
We identified two glass phases formed in three undercooled liquids of elemental Ag, binary Cu-Ag, and binary Cu-Zr alloys using molecular dynamics (MD) simulations: • the homogeneous L-phase arises from quenching quickly from high temperature liquid • the heterogeneous solid-like G-phase arises from the isothermal equilibration at temperatures below the melting point. The G-phase exhibits a core-shell structure with the ordered cores surrounded by percolating liquid-like shells. The distinguishable structures between these two phases are expected to different mechanical behavior. The present study reports MD simulations to compare the shear deformation of these two phases in binary Cu2Zr system. At room temperature, the G-phase exhibits a higher critical stress, a higher critical strain, and higher shear modulus than the L-phase, suggesting that the G-phase has improved strength and rigidity compared to the homogeneous L-phase. The plastic yielding mechanism of both the G-phase and L-phase is accompanied by shear band formation. However, the formation of shear band in G-phase is confined by the cores to a highly localized region and characterized by local mechanical melting. In contrast, the shear band in L-phase exhibits greater width and much more homogenous character. We conclude that the mechanical properties of a metallic glass will vary significantly according to the type of glassy phase formed during processing.